ANTIDIABETIC AND BIOLOGICAL ACTIVITIES OF NICOTIANA TABACUM: POSSIBLE MECHANISMS - OGUNTIBEJU, OLUWAFEMI OMONIYI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Diabetes mellitus is a growing global health problem. Reports predicted that diabetes mellitus could reach a pandemic level affecting people in both developing and developed countries. According to the World Health Organization, high blood glucose is seen as the third highest risk factor for premature mortality in diabetics. For several thousands of years before the adventure of orthodox medications, human beings have been using medicinal plants in the treatment of various disease conditions such as cancer, cardiovascular disease, infertility, bacterial, viral infections, and diabetes mellitus. The beneficial effects of selected medicinal therapies in the treatment and management of diabetes and diabetic complications have been reported. Many medicinal plants across Africa and Asia are known for their rich phytochemicals with effective components that have been observed to effectively reduce high blood glucose either in diabetic persons or diabetes-induced animals. The motivation for the use of medicinal plants includes availability, affordability, knowledge, effectiveness, and safety and some are of the opinion that medicinal plants and their derivatives could be effective and safe alternative treatment for diabetes and diabetic complications. Nicotiana tabacum is one of those plants with antidiabetic and pharmacological potentials which could benefit humans and animals if appropriately utilized; however, less attention has been focused on its antidiabetic properties. In fact, there is a paucity of information on the antidiabetic activities of N. tabacum. Therefore, this paper examines the antidiabetic and other biological activities of N. tabacum.